2013
DOI: 10.1177/0885066613510874
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Pilot Study of Dexmedetomidine Versus Midazolam for Intensive Care Unit Sedation

Abstract: Transitioning benzodiazepine sedation to dexmedetomidine when patients qualify for daily awakenings may reduce the development of delirium and facilitate remembrance of ICU experiences but may lead to manifestations of ASD. Monitoring hypotension is required for both the sedatives. Additional comparative studies focusing on the long-term impact of ICU recall and psychological outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Twenty-seven articles were excluded because 20 investigated sedation protocol that the type of sedative drugs could not be identified, 4 studies were secondary analysis of previous reports, and 3 were study protocols. As a result, a total of 51 citations comprising 52 RCTs were included in our analysis141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364. The article by Jakob and colleagues comprised two RCTs38.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven articles were excluded because 20 investigated sedation protocol that the type of sedative drugs could not be identified, 4 studies were secondary analysis of previous reports, and 3 were study protocols. As a result, a total of 51 citations comprising 52 RCTs were included in our analysis141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364. The article by Jakob and colleagues comprised two RCTs38.…”
Section: Resultsmentioning
confidence: 99%
“…46 MacLaren et al showed a lower incidence of delirium without more adverse reactions. 47 Ozaki et al studied the use of continuous infusion of dexmedetomidine in pediatric setting, for longer than the recommended time of 48 hours and at doses of 0.7 mcg/kg/h. The patients reached a good level of sedation with the use of the drug for nearly 6 days, with no more adverse events, rebound symptoms or abstinence.…”
Section: Resultsmentioning
confidence: 99%
“…Although these medications are intended to reduce stress, anxiety, and oxygen consumption, they often produce long periods of unconsciousness. Further, the efficacy of these medications for symptom management is questionable; patients still report persistent symptoms of anxiety and pain 5,9 while receiving these medications, leading to increased doses for extended periods without any clear benefit. 10 Anxiety requires ongoing symptom management throughout the course of mechanical ventilation because patients continue to report moderate anxiety regardless of the duration of mechanical ventilation and despite receiving sedative medications.…”
Section: Background and Significance Of Anxiety In Critically Ill Patmentioning
confidence: 99%
“…10 Anxiety requires ongoing symptom management throughout the course of mechanical ventilation because patients continue to report moderate anxiety regardless of the duration of mechanical ventilation and despite receiving sedative medications. 4,9,10 Current research on ICU symptoms and sedation management focuses on pharmacological strategies only to manage patients' symptoms despite the documented deleterious effects of sedative agents such as hypotension, delayed weaning, immobility, and delirium. [2][3][4][5][6][7][8][9][10] However, it is recommended that symptoms of ICU patients receiving mechanical ventilation be managed without sedation 11 or if necessary, with minimum use of sedative agents, giving the brain a chance to clear the medications acting on the central nervous system.…”
Section: Background and Significance Of Anxiety In Critically Ill Patmentioning
confidence: 99%
See 1 more Smart Citation